1970
DOI: 10.1152/ajplegacy.1970.218.4.1128
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of ADH in conscious and anesthetized dogs

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
2

Year Published

1973
1973
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 0 publications
0
33
2
Order By: Relevance
“…However, the results of chronic experiments such as these are obviously not directly comparable with those of the present investigation in which the period studied after haemorrhage was of relatively short duration. The mean prehaemorrhage plasma vasopressin concentration in the Long Evans rats was relatively high, presumably because of anaesthesia and the stress of surgery (Bonjour & Malvin, 1970 (Valtin, Sawyer & Sokol, 1965;Jones & Lee, 1967;Lee & Williams, 1972), and since oxytocin has measurable antidiuretic activity if released in sufficient quantity (Bisset & Lewis, 1962), the present finding supports the view that haemorrhage stimulates the independent release of vasopressin (Chaudhury & Walker, 1958;Ginsburg & Smith, 1959;Beleslin et al 1967;Schrier, Verroust, Jones, Fabian, Lee & de Wardener, 1968).…”
Section: Discussionmentioning
confidence: 95%
“…However, the results of chronic experiments such as these are obviously not directly comparable with those of the present investigation in which the period studied after haemorrhage was of relatively short duration. The mean prehaemorrhage plasma vasopressin concentration in the Long Evans rats was relatively high, presumably because of anaesthesia and the stress of surgery (Bonjour & Malvin, 1970 (Valtin, Sawyer & Sokol, 1965;Jones & Lee, 1967;Lee & Williams, 1972), and since oxytocin has measurable antidiuretic activity if released in sufficient quantity (Bisset & Lewis, 1962), the present finding supports the view that haemorrhage stimulates the independent release of vasopressin (Chaudhury & Walker, 1958;Ginsburg & Smith, 1959;Beleslin et al 1967;Schrier, Verroust, Jones, Fabian, Lee & de Wardener, 1968).…”
Section: Discussionmentioning
confidence: 95%
“…The anti-diuretic activity of the plasma in the rat, cat and dog is elevated during anaesthesia with ether, urethane and with many barbiturates (Dicker, 1953;Ginsberg & Brown, 1957;Beleslin, Bisset, Haldar & Polak, 1966;Bonjour & Malvin, 1970). Chloralose has been reported not to increase anti-diuretic activity of plasma (Ginsberg & Brown, 1957).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of sensitive techniques for AVP measurement by radioimmunoassay has given fresh impetus to this re-evaluation. 9 In the case of opioids the relationship with the release of AVP is uncertain, as is shown by the work of Aziz, et al These authors demonstrated that the response of plasma AVP to the intracerebroventricular administration of morphine is both dose and time dependent. Small doses of morphine inhibit and larger doses first stimulate and then subsequently inhibit the release of AVP.…”
Section: Discussionmentioning
confidence: 99%